Interactive Teaching in Higher Education for Effective Knowledge Dissemination and Improved Student Participation - Pawar, Atmaram P.; Dhapte-Pawar, Vividha V.; Gaikwad, Vinod L. (Indian Journal of Pharmaceutical Education and Research, 2021)
The present generation of students has information at their hands with the advances in technology. The conventional teaching in monologue manner, just delivering bookish information and dictation are ineffective to inculcate knowledge and confidence in them. Attendance is another major challenge for the current educational system. Assessment patterns have improved from ‘marking’ to ‘continuous grading’ systems. However, the questions in examinations merely evaluate the memorizing and writing skills of the students. There is limited scope for students to think in a scientific and logical manner. In addition, there is a need for teaching-learning beyond the classrooms in emergencies like the prevailing pandemic of Coronavirus Disease / COVID-19. The adoption of Information and Communication Technology (ICT) tools will not suffice all these requirements. Interactive teaching-learning would help to convert bookish information into life-long knowledge. Case-based problem-solving questions would create the need for thinking. The blending of skills and knowledge will inculcate value and confidence in students along with their university degrees. A pre-study perception survey was performed to understand the educational needs of students and expectations of parents and the pharma industry, followed by activities to promote interactive teaching-learning in a selected institute. The post-study feedback survey revealed interesting results, which will, boosts effective knowledge dissemination along with improved student attendance.
Keywords: Interactive; Teaching; Learning; Thinking; Examination